2015
DOI: 10.1161/atvbaha.114.305095
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Mutation Leads to Valvular Calcification Through Enhanced Myofibroblast Mechanotransduction

Abstract: Objective Calcific aortic valve disease (CAVD) is a significant cardiovascular disorder, and controversy exists as to whether it is primarily a dystrophic or osteogenic process in vivo. In this study, we sought to clarify the mechanism of CAVD by assessing a genetic mutation, Notch1 heterozygosity, which leads to CAVD with 100% penetrance in humans. Approach and Results Murine immortalized Notch1+/− aortic valve interstitial cells (AVICs) were isolated and expanded in vitro. Molecular signaling of wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 53 publications
(71 reference statements)
2
36
0
Order By: Relevance
“…Myofibroblastic phenotype might be the intermediate state of osteoblastic phenotype [21]. Recent study also supported this point in which reduced Notch1 signaling promoted VIC myofibroblastic differentiation and then dystrophic calcification [22]. In the present study, we demonstrated that IL-18 could induce the myofibroblastic transition of VICs, as evidenced by upregulation of α-SMA and enhanced fiber formation.…”
Section: Discussionsupporting
confidence: 81%
“…Myofibroblastic phenotype might be the intermediate state of osteoblastic phenotype [21]. Recent study also supported this point in which reduced Notch1 signaling promoted VIC myofibroblastic differentiation and then dystrophic calcification [22]. In the present study, we demonstrated that IL-18 could induce the myofibroblastic transition of VICs, as evidenced by upregulation of α-SMA and enhanced fiber formation.…”
Section: Discussionsupporting
confidence: 81%
“…In order to define the role of Notch1 in AVICs, immortalized aortic VICs were isolated from Notch1 +/− Immortomice, a compound mutant mouse which is both heterozygous for Notch1 and expresses the immortalizing oncogene simian virus 40 (SV40) large tumor (T) antigen (Ag), and were found to not only have molecular differences at baseline but also had an exaggerated response to cyclic mechanical strain, which mimics in vivo diastolic loading, becoming fully activated and resulting in calcification [41]. Further mechanistic insight was found by studying calcified human aortic valves, where the long non-coding RNA, lncRNA H19 , was identified as a NOTCH1 repressor with a direct role in calcification of human aortic VICs.…”
Section: Molecular Pathways For Aortic Valve Calcificationmentioning
confidence: 99%
“…98 Aortic valve interstitial cells from Notch1 heterozygous deficient mice become fully activated myofibroblasts leading to enhanced dystrophic calcification. 99 Genetic ablation of CaV3.2 channels enhances the arterial myogenic response through modulation of the RyR-BKCa (ryodine receptors-large conductance Ca 2+ -activated K + channels) axis. 100 Conditional knockout of the E-twenty six factor Ets variant 2 in endothelial cells resulted in impaired neovascularization in response to ischemic tissue injury.…”
Section: Defining Atherosclerosis In Animal and Cellular Modelsmentioning
confidence: 99%